A bluetooth educational content distribution system modelled on a service-oriented architecture - Bugembe, Kamulegeya Grace (Department of Computer Science, 2023)
In this research, we design and prototype an educational content distribution system modeled on a Service-Oriented Architecture (SOA) paradigm and implemented using Web services, XML and Bluetooth technology. In the prototype, we use an Open Source Learning Management System (LMS) Sakai implemented in Java and branded Vula for the University of Cape Town (UCT). Web services and its specification of SOAP, XML and Bluetooth technology are used to integrate the disparate technologies that form the service architecture. The disparate technologies include among others Bluetooth enabled mobile phones and PDAs, services (modules) which may be running on different operating systems, and deployed over Local Area Networks (LANs) or Internet. The service is meant to leverage the existing infrastructure to provide a new, cheap channel for education content distribution to mobile devices in learning institutions especially Universities in the developing world and Africa in particular. We design, implement and evaluate the prototype for performance and scalability. During the designing and implementation of the architecture, we incorporate SOA principles of service/module re-use, service composition, loose-coupling, standard data exchange within the system or services, and extensibility of the services among others. The aim of the service is to distribute education content uploaded in Learning Management Systems (LMSs) to Bluetooth enabled mobile devices that are increasingly held by students in developing world Universities. The service is intended to supplement existing Web-based and lecture room content distribution channels by opening up the mobile device space. For the prototype, we focus on repackaging structured text content and distributing it to Bluetooth enabled phones and PDAs using Bluetooth technology. We evaluate our prototype for performance using experimental studies.